2, 4, 6‐Triamino‐1, 3, 5‐Trinitrobenzene Explosive Wastewater Treatment by Hydrodynamic Cavitation Combined with Chlorine Dioxide. Issue 8 (14th May 2020) - Wang, Kun; Jin, Riya; Qiao, Yina; He, Zengdi; Wang, Xiaojian; Wang, Chaoqi; Lu, Yanrong
Abstract: A large amount of wastewater is produced in the process of 2, 4, 6‐Triamino‐1, 3, 5‐trinitrobenzene (TATB) production, which is harmful to the environment and human health. In this work, the removal rate of chemical oxygen demand (COD) from TATB wastewater was investigated by using hydrodynamic cavitation (HC), chlorine dioxide (ClO2 ), and the combination of the HC and ClO2 . We explored the effects of different operating parameters on extent of degradation including time (10–60 min), concentration of ClO2 (25–150 mg/L) and initial pH (6, 9.25). The result showed that the reduction of COD from explosive wastewater with initial concentration of 5407 mg COD/L was 65.9 % after a 60 min treatment with a ClO2 dosage of 150 mg/L at a pH of 6. The COD removal process by the HC/ClO2 conforms to a pseudo‐first‐order kinetic equation with a reaction rate of 20.8×10 −3 min −1 . We were able to determine that the HC/ClO2 method has a synergistic effect on TATB wastewater treatment with a synergetic coefficient of 3.01. By comparing the cavitational yield and cost of each process, the HC/ClO2 has a higher energy efficiency (26.78×10 −3 mg/J). In conclusion, the HC/ClO2 composite process is more economical, effective, and suitable for large‐scale commercial operations. Abstract :